2017
DOI: 10.1037/aca0000089
|View full text |Cite
|
Sign up to set email alerts
|

Leisure reading and social cognition: A meta-analysis.

Abstract: Does reading a single passage of literary fiction really improve theory of mind? An attempt at replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
151
6
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(198 citation statements)
references
References 64 publications
19
151
6
4
Order By: Relevance
“…Considering that reading volume is cumulative over a lifetime (Stanovich, West, & Harrison, ), most research examining associations with reading volume has focused on adult participants, such as university students. In this older population, positive associations are shown between reading in one's free time and social understanding (Mar, Oatley, Hirsh, dela Paz, & Peterson, ; Mar, Oatley, & Peterson, ; Mumper & Gerrig, ). In studies such as these, social understanding is often measured by whether participants can identify actors’ mental states by looking only at their eyes (the Reading the Mind in the Eyes Test; Baron‐Cohen, Wheelwright, Hill, Raste, & Plumb, ).…”
Section: Reading and Social Understandingmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that reading volume is cumulative over a lifetime (Stanovich, West, & Harrison, ), most research examining associations with reading volume has focused on adult participants, such as university students. In this older population, positive associations are shown between reading in one's free time and social understanding (Mar, Oatley, Hirsh, dela Paz, & Peterson, ; Mar, Oatley, & Peterson, ; Mumper & Gerrig, ). In studies such as these, social understanding is often measured by whether participants can identify actors’ mental states by looking only at their eyes (the Reading the Mind in the Eyes Test; Baron‐Cohen, Wheelwright, Hill, Raste, & Plumb, ).…”
Section: Reading and Social Understandingmentioning
confidence: 99%
“…Because social understanding relies fundamentally on making inferences about others’ mental states, a third explanation centers on readers’ opportunities to generate such inferences about characters in a book and thus hone their inferencing abilities (Mar, Oatley, Djikic, & Mullin, ; Mumper & Gerrig, ). Generally, inferencing involves drawing a connection or understanding an implication that is not explicitly stated (Van Kleeck, ).…”
Section: But What Explains the Connection?mentioning
confidence: 99%
“…the Author Recognition Test ) and self‐report measures of empathy. Consistent with such findings, a recent meta‐analysis (Mumper & Gerrig, ) showed that fiction reading indeed had a higher correlation with measures of social cognition, compared to nonfiction reading . However, correlational studies preclude any inferences of causality, hence we cannot say whether lifetime exposure to literature (i.e.…”
Section: Introduction: Empathy and Literary Readingmentioning
confidence: 57%
“…This is an opportunity to meet other perspectives on books-and how they affect people's lives-by starting a dialogue about differences and similarities in how stories are received by readers with different cultures that share the same passion. The prosocial effect that fiction has [104][105][106] is complemented by the opportunity of actual social interaction offered by digital social reading practices. Further research will need to assess whether social reading is indeed enhancing the prosocial effect of fiction.…”
Section: Readersmentioning
confidence: 99%